Pengelolaan Laboratorium Komputer dalam Meningkatkan Kemampuan Menguasai Teknologi Informasi Peserta Didik di SMK NU Pelita Nusantara - Moh. Luthfi Aditiya Hidayat (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2025)
The computer laboratory management is very important and influential on students' information technology competence and the teaching and learning process. This study aims to describe the management of computer laboratories in improving the ability to master information technology of students at SMK NU Pelita Nusantara. This research uses a qualitative approach, data collection techniques through observation, interviews or interviews and documentation. The data analysis technique used is data reduction, data presentation, and data verification. The results of this study indicate that the management of computer laboratories in learning computer information technology at SMK NU Pelita Nusantara is by caring for tools in computer laboratories by organizing and maintaining existing facilities, compiling equipment programs needed in computer laboratories and compiling laboratory rules.